Normal Pediatric Kidney Dimensions on Multidetector CT: Defining Standards for Pakistani Children: Normal Pediatric Kidney Dimensions on Multidetector CT in Pakistani Children - Yousaf, Muhammad; Mirza, Waseem Akhtar; Alam, Muhammad Masood; Islam, Faizan Ul; Rasheed, Aisha; Zafar, Burhan; Sajjad, Maryam; Aman, Muhammad; Hassan, Ayesha; Khan, Memoona (Pakistan Journal of Health Sciences, 2026)
Kidney size in children is a key marker for detecting congenital abnormalities and conditions that may develop later. In South Asia, CT-based normative data are limited. Objectives: To establish CT-derived reference ranges for renal size in Pakistani children and examine their relationship with somatic measurements. Methods: This retrospective study examined 15 years of data (2010–2024) from Aga Khan University Hospital, Karachi, focusing on CT scans conducted with GE 128-slice or Toshiba 640-slice scanners. The study included children aged one week to 16–17 years, categorized by age, and utilized both descriptive and inferential statistics. Results: Kidney size in children is a key marker for detecting congenital abnormalities and conditions that may develop later in life. The right kidney volume rises from about 19 cm³ in infants to 146 cm³ in late adolescence, while the left kidney grows from approximately 21 cm³ to 146 cm³. There is a strong correlation between renal size and factors like age, height, weight, and body surface area (p<0.001). No significant differences were observed between sexes, and multiple regression analysis confirmed these associations with significant models for both kidneys. Conclusions: This study provides the first CT-based reference ranges for renal dimensions in Pakistani children. Renal volume rises consistently with age and strongly correlates with somatic factors, offering valuable benchmarks for clinical assessment.